Author Response: Association of Sleep, Neuropsychological Performance, and Gray Matter Volume With Glymphatic Function in Community-Dwelling Older Adults. (14th February 2023) - Siow, Tiing Yee; Toh, Cheng Hong; Hsu, Jung-Lung; Liu, Geng-Hao; Lee, Shwu-Hua; Chen, Ning-Hung; Fu, Changjui James; Castillo, Mauricio; Fang, Ji-Tseng
Abstract : We appreciate the insightful comments on our study. 1 Contrast-based imaging allows direct visualization of the glymphatic system and assessment of its function based on the pharmacokinetics of contrast agents. However, quantifications of glymphatic activity in individual fluid compartments may require other techniques.